Sharia Economic Law in The Theory Of Legal Realism - Syarif, Kurnia Ali (Pinisi Journal of Social Science, 2025)
This article aims to discuss the concept of legal theory of realism and its influence on Islamic economic law in Indonesia. The approach applied in this article is a qualitative approach with a descriptive analysis method. The results of this study are as follows: First, legalism is a theory that we believe is not just the number of rules in the law, but also not only that it is not applied, but is actually realistic. Legal realism views law as the result of court decisions, accepts facts as elements in the creation of legal norms, and recognizes the existence of metaphysical or logical ideas. Realism has two legal requirements. In other words, legal realism in America and rights realism in Scandinavia follow the principles of legal realism. Second, this legal theory of realism has a certain harmony with Islamic law and has found its place in Islamic business law in Indonesia. One example is the fatwa decision in Islamic business law, which revitalizes the social conditions of society in determining norms